A Quasi-Experimental Study of a Movement and Preliteracy Program for 3- and 4-Year-Old Children - Bedard, Chloe; Bremer, Emily; Campbell, Wenonah; Cairney, John (Frontiers in Pediatrics, 2017)
Objective: Approximately 28% of children are not ready for kindergarten, 91% are inactive according to current guidelines, and 21% are overweight/obese. Early intervention to strengthen movement and pre-literacy skills may help to curb the concerning rates of poor school readiness, inactivity, obesity, and subsequently positively impact health across the lifespan. The objective of this pilot study was to evaluate the effectiveness of a motor and pre-literacy skill program for a community sample of 3-4 year old children. Methods: A quasi-experimental study design was used. The program was run for one hour/week for 10 weeks and consisted of movement skill instruction, free-play, and an interactive reading circle with care-giver involvement throughout each session. Movement and pre-literacy skills were assessed in all children pre- and post-intervention using the Peabody Developmental Motor Scales-2, the Preschool Word and Print Awareness tool, and the Phonological Awareness Literacy Screening Tool. Results: Nineteen families (experimental group, n=8; control group, n=11) were recruited (Mean age=3yrs, 8m; 47% male). There was a significant effect of group on gross motor raw scores overall (F (1, 16)=4.67, p<.05; ωp2 = .16) and print-concept knowledge (F (1, 16)=11.9, p<.05; ωp2 =.38). Conclusions: This study was one of the first to examine the impact of a community-based movement skill and pre-literacy program with care-giver involvement in preschool children. Future research should continue to explore the effects of the program with larger and more diverse samples on multiple health and developmental outcomes.